First principles calculations of indium impurity-cadmium vacancy complex in CdTe - Yuriychuk, I.; Solodin, S.; Fochuk, P. (Functional Materials, 2018)
First principles calculations are used to study stability of the complex formed by indium impurity and cadmium vacancy in CdTe. Formation energies and transition energy levels of the cadmium vacancy, indium impurity and their complex in different charge states are calculated using supercell method within density functional theory in the local density approximation. From the analysis of binding energy of the complex it is found that formation of the complex is favorable and the neutral and single charged states of the complex are stable. The studies of the formation energy as a function of the Fermi level show that interaction between the shallow indium impurity and cadmium vacancy results in the Fermi level pinning near the middle of the semiconductor band gap and leads to the formation of semi-insulating material.